Energy Efficient Novel Sizing of Jute Yarns. Issue 2 (3rd March 2016) - Chakrabarti, S. K.; Saha, S. G.; Basu, S.; Mukhopadhyay, G.; De, S.; Sanyal, P.; Ray, P.
Abstract : A novel tapioca starch (TS)-based energy efficient natural sizing technology for sizing jute yarn was developed. The performance of the developed formulation was tested in a laboratory at pilot scale and subsequently validated through industrial-level shop floor trials vis-à-vis the conventional tamarind kernel powder (TKP)-based sizing. Unlike TKP sizing, the developed natural size paste formulation did not require "cooking" at elevated temperature, and could be maintained at room temperature in sow box. In addition, TS-based sized yarns could be dried at lower temperature. TS-sized jute yarns showed better abrasion resistance, and slightly better tensile strength values when compared with conventional TKP-sized yarns. TS-based sized jute yarns exhibited better elastic recovery compared with TKP-sized yarns under cyclic loading. The sizing effluents were found to be drastically reduced in TS-based recipe showing lower Biological Oxygen Demand and Chemical Oxygen Demand. Using TS-based sizing formulation, industrial trials conducted at shop floor demonstrated reduction in warp breakage, higher energy efficiency, cost competitiveness, and lower eco-burden.